Global legal trends in fertility interventions: A criminal justice perspective - Hakobyan, Anush (Edelweiss Applied Science and Technology, 2024)
The global decline in birth rates has heightened the urgency of addressing infertility, a condition that affects approximately one in six individuals worldwide. This paper explores the complex causes of infertility, including genetic predispositions, lifestyle choices, and environmental exposures, which collectively contribute to reproductive challenges in both men and women. The advent of Assisted Reproductive Technologies (ART), particularly In Vitro Fertilization (IVF), has revolutionized infertility treatment since 1978, providing hope to millions. Despite the remarkable advancements in ART, these technologies raise significant legal and ethical concerns, necessitating robust regulatory frameworks. This paper examines the historical development of ART, with a focus on global trends and data from ART registries, highlighting the steady increase in ART cycles worldwide. Furthermore, it delves into the legal and ethical challenges associated with ART, including issues related to donor rights, parental responsibilities, and the potential health risks for children born through these technologies. The paper advocates for continued refinement of ART practices and regulations to ensure safety, efficacy, and ethical integrity. It also underscores the importance of ongoing research into the long-term health implications for children conceived via ART and the broader societal impacts. By addressing these concerns, ART can continue to offer a viable solution to infertility while upholding human dignity and societal well-being.